Optimalisasi Bauran Pemasaran Madu Kelulut di Serdang Selangor Malaysia Menggunakan Metode 6P - M. Dio Fadhila Yulas; Juita Rahmadani Manik; Siti Nurathirah Abu Hassan (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Kelulut honey, produced by stingless bees such as Heterotrigona itama and Geniotrigona thoracica, is increasingly in demand in Malaysia due to its distinctive flavor and health benefits. This study aims to identify marketing strategies for kelulut honey in Serdang, Selangor, Malaysia, using the 6P marketing mix approach (Product, Price, Place, Promotion, People, and Process). Primary data were collected through in-depth interviews with kelulut honey entrepreneurs and field observations at the Malaysian Agriculture Horticulture & Agrotourism Show (MAHA), while secondary data were obtained from various relevant publications. The results show that product innovation, value-based pricing strategy, diversification of distribution channels through online and offline platforms, creative promotion, human resource development, and production process efficiency are the main factors in improving the competitiveness of kelulut honey. This approach can strengthen product positioning in domestic and international markets, increase consumer loyalty, and support industry sustainability. With the implementation of an integrated strategy, the kelulut honey industry has the potential to grow more rapidly, contributing significantly to the welfare of the community, especially smallholder farmers.